Traditional foods with their constituent's antiviral and immune system modulating properties. Issue 1 (January 2021) - Rahman, Md. Mahbubur; Mosaddik, Ashik; Alam, AHM Khurshid
Abstract: Background: Viruses are responsible for several diseases, including severe acute respiratory syndrome, a condition caused by today's pandemic coronavirus disease (COVID-19). A negotiated immune system is a common risk factor for all viral infections, including COVID-19. To date, no specific therapies or vaccines have been approved for coronavirus. In these circumstances, antiviral and immune boosting foods may ensure protection against viral infections, especially SARS-CoV-2 by reducing risk and ensuring fast healing of SARS-CoV-2 illness. Scope and approach: In this review, we have conducted an online search using several search engines (Google Scholar, PubMed, Web of Science and Science Direct) to find out some traditional foods (plant, animal and fungi species), which have antiviral and immune-boosting properties against numerous viral infections, particularly coronaviruses (CoVs) and others RNA-virus infections. Our review indicated some foods to be considered as potential immune enhancers, which may help individuals to overcome viral infections like COVID-19 by modulating immune systems and reducing respiratory problems. Furthermore, this review will provide information regarding biological properties of conventional foods and their ingredients to uphold general health. Key Findings and Conclusions: We observed some foods with antiviral and immune-boosting properties, which possess bioactive compounds that showed significant antiviral properties against different viruses, particularly RNA viruses such as CoVs. Interestingly, some antiviral and immune-boosting mechanisms were very much similar to the antiviral drug of COVID-19 homologous SARS (Severe Acute Respiratory Syndrome Coronavirus) and MERS (Middle East Respiratory Syndrome Coronavirus). The transient nature and the devastating spreading capability of COVID-19 lead to ineffectiveness of many curative therapies. Therefore, body shielding and immune-modulating foods, which have previous scientific recognition, have been discussed in this review to discern the efficacy of these foods against viral infections, especially SARS-CoV-2. Abstract : Traditional foods; Antiviral activity; Immune-stimulating; Infectious; Coronaviruses; General health.